Program Calistung (Baca, Tulis Dan Hitung) Dengan Pendekatan Akademik Eksperiensial Untuk Meningkatkan Pengetahuan Sosial Budaya Di Sanggar Bimbingan Kampung Gumut, Malaysia - Muchammad Ibnu Muzakir; Idham; Rokimin (Universitas Darunnajah, Jakarta, Indonesia, 2024)
Malaysia is the country that is used as the largest place for Indonesian citizens to look for work. Some of the PMI enter through illegal channels, so that the PMI children cannot register for school. Sanggar Guidance Kampung Gumut is one of the schools that provides opportunities for PMI children to illegally receive an education, but unfortunately there are still many SB children from Gumut village who still cannot read, write and count. Therefore, KKN activities were carried out there with the aim of improving the reading, writing and arithmetic skills of SB children in Gumut village. The implementation of KKN at SB Kampung Gumut was carried out from 17 January to 28 January 2024, where the methods used were preparation, socialization, implementation of activities and observation. Based on the KKN that was carried out, the results showed that there were around 23 children in SB Kampung Gumut. These children do not yet have good skills in calistung, reading the Koran and reading prayers. So the author carried out several activities in accordance with these problems. Based on the results of the guidance that has been carried out after carrying out the calistung program, the children of SB Kampung Gumut can read, write and count at a basic level, and are able to read iqra and pronounce the reading well.